2015
DOI: 10.1007/s12550-015-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin production by Aspergillus fumigatus strains from animal environment. Micro-analytical sample treatment combined with a LC-MS/MS method for gliotoxin determination

Abstract: In this study, gliotoxin production by Aspergillus fumigatus strains from animal environment is studied. Moreover, a rapid, easy and environment-friendly micro-analytical sample treatment procedure coupled with LC-MS/MS was applied for the determination of gliotoxin from A. fumigatus cultures. The ability of gliotoxin production by 143 strains was assayed in yeast extract sucrose agar, and 1 ml of chloroform was used for toxin extraction without further clean-up. Mean recoveries at two spiking levels (2500 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
2
0
0
Order By: Relevance
“…Analysis of a gliotoxin standard (Fig. 1C) showed that it elutes at 3.30 min with an accurate mass of 327.0464 Da (2.8 ppm) and has key fragments of 263.1 Da and 245.1 Da, in accord with values reported in the literature (20).…”
supporting
confidence: 85%
“…Analysis of a gliotoxin standard (Fig. 1C) showed that it elutes at 3.30 min with an accurate mass of 327.0464 Da (2.8 ppm) and has key fragments of 263.1 Da and 245.1 Da, in accord with values reported in the literature (20).…”
supporting
confidence: 85%
“…Analysis of a gliotoxin standard ( Fig. 1C ) showed that it elutes at 3.30 minutes, with an accurate mass of 327.0464 Da (2.8 ppm) and has key fragments of 263.1 Da and 245.1 Da, in accord with values reported in the literature (18).…”
Section: Figsupporting
confidence: 85%
“…Gliotoxin ( Figure 8A ), a mycotoxin produced by Aspergillus fumigatus , can cause immunosuppression, genotoxicity, cytotoxicity, and apoptosis ( Pena et al, 2015 ). Gliotoxin is synthesized by the gliotoxin oxidase GliT and can therefore be reverse degraded via its synthetic pathway ( Dolan et al, 2017 ).…”
Section: Common Mycotoxins and Corresponding Enzymes Used For Detoxif...mentioning
confidence: 99%